2021
DOI: 10.1038/s41598-021-03439-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrical response of retinal ganglion cells in an N-methyl-N-nitrosourea-induced retinal degeneration porcine model

Abstract: Retinal prosthesis is regarded as the treatment for vision restoration in the blind with retinal degeneration (RD) due to the loss of photoreceptors. A strategy for retinal prosthesis is to electrically activate surviving neurons. The retina’s response to electrical stimulation in a larger RD model has not been studied yet. Therefore, in this study, we investigated electrically evoked retinal responses in a previously validated N-methyl-N-nitrosourea (MNU)-induced porcine RD model. Electrically evoked response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our results showed that RGCs in the RD retina produced fewer spikes than in the WT retina ( Figure 8 ). In vitro studies using the mouse, rat, and pig models reported that fewer RGC spikes are evoked in the RD retina than in the WT retina with electrical stimulation ( Goo et al, 2011b ; Jensen, 2012 ; Cha et al, 2021 ). In vivo studies in human subjects also showed that higher stimulus intensity was required to induce phosphenes in patients with RP than in people with normal vision ( Delbeke et al, 2001 ; Gekeler et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that RGCs in the RD retina produced fewer spikes than in the WT retina ( Figure 8 ). In vitro studies using the mouse, rat, and pig models reported that fewer RGC spikes are evoked in the RD retina than in the WT retina with electrical stimulation ( Goo et al, 2011b ; Jensen, 2012 ; Cha et al, 2021 ). In vivo studies in human subjects also showed that higher stimulus intensity was required to induce phosphenes in patients with RP than in people with normal vision ( Delbeke et al, 2001 ; Gekeler et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…This induces a less reliable RGC response to repetitive electrical stimulation ( Ho et al, 2020 ; Yoon et al, 2020 ). Therefore, higher stimulation intensities may be required to electrically activate degenerate RGCs than that required for normal RGCs ( Jensen and Rizzo, 2009 ; Goo et al, 2011b ; Cha et al, 2021 ). However, all previous experiments have focused on the single RGC level response, not the population of RGC responses.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, it is well-known that a long-duration pulse (over 1000 µs) more effectively induces a network-mediated RGC response due to voltage-gated Ca 2+ channels in BCs [35]. However, our data showed that RGC spikes in RD monkeys and RD pigs [36] were not well induced when we applied a long pulse duration above 1000 µs (Figure 5). We hypothesize that the inhibitory input with GABA by electrically activated surviving horizontal cells (HCs) to BCs and RGCs limits spike firing in the RD.…”
Section: Discussionmentioning
confidence: 53%